1976
DOI: 10.1073/pnas.73.10.3584
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between in vitro cellular aging and in vivo human age.

Abstract: Differences between early and late passage cell cultures on the organelle and macromolecular levels have been attributed to cellular "aging." However, concern has been expressed over whether changes in diploid cell populations after serial passage in vitro accurately reflect human cellular aging in vivo. Studies were therefore undertaken to determine if significant differences would be observed in the in vitro lifespans of skin fibroblast cultures from old and young normal, nonhospitalized volunteers and to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
184
4
4

Year Published

1979
1979
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(219 citation statements)
references
References 18 publications
(23 reference statements)
27
184
4
4
Order By: Relevance
“…A cross-sectional study by Martin et al (1970) revealed such an effect, with an average reduction in lifespan of 0.2 population doublings per year of age, although there was considerable variability within each age group. A similar difference was also reported in a comparison of cultures from young (21-36 years) and old (63-92 years) donors (Schneider and Mitsui 1976). A further correlation between in vitro and in vivo ageing was found by Smith et al (1978) in studies on age-related changes in colony size distributions among individual fibroblasts.…”
Section: Do Somatic Cells Really Age?supporting
confidence: 78%
“…A cross-sectional study by Martin et al (1970) revealed such an effect, with an average reduction in lifespan of 0.2 population doublings per year of age, although there was considerable variability within each age group. A similar difference was also reported in a comparison of cultures from young (21-36 years) and old (63-92 years) donors (Schneider and Mitsui 1976). A further correlation between in vitro and in vivo ageing was found by Smith et al (1978) in studies on age-related changes in colony size distributions among individual fibroblasts.…”
Section: Do Somatic Cells Really Age?supporting
confidence: 78%
“…In vitro, fetal and neonatal skin fibroblasts have greater proliferative capacity than adult or aged samples (Bruce et al 1986;Schneider and Mitsui 1976;Martin et al 1970). In addition, fibroblasts in culture lose their proliferative capacity after a number of passages, and when senescence is achieved they are unable to proliferate.…”
Section: Discussionmentioning
confidence: 99%
“…The kinetics of fibroblast growth have been extensively studied in vitro (Bruce et al 1986;Schneider and Mitsui 1976;Martin et al 1970). Studies suggest that proliferation and apoptosis are linked and are developmentally regulated.…”
mentioning
confidence: 99%
“…Si mutaciones somáticas impiden que la célula senescente salga del ciclo celular, las divisiones celulares mantenidas, asociadas a una disfunción del telómero, ocasionarían gran inestabilidad genómica conocida como "crisis del telómero" 17 . Por otro lado, este fenómeno de senescencia celular aumenta la resistencia a la apoptosis 16 otro lado, la declinación en la respuesta inmune observada con el envejecimiento favorecería el desarrollo de neoplasias debido a la tolerancia inmune [18][19][20] . Mecanismos epigenéticos, como la hipermetilación de islas CpG (citosina-guanina) cercana a zonas promotoras, han mostrado ser un mecanismo común de silenciamiento de genes supresores de tumores progresivo con la edad 21 .…”
Section: Edad Y Cáncerunclassified